2009
DOI: 10.1002/xrs.1142
|View full text |Cite
|
Sign up to set email alerts
|

Trace element profiling of gunshot residues by PIXE and SEM‐EDS: a feasibility study

Abstract: We critically compare particle induced X-ray emission (PIXE) on the ion microprobe with scanning electron microscopy with energy dispersive X-ray spectroscopy (SEM-EDS) for the characterisation of gunshot residues (GSR). Samples of gunshot residue from several different firearms were collected. Individual particles of GSR were analysed by SEM-EDS using a 30keV electron beam focussed to ~10nm and PIXE using a 2.5MeV proton beam focussed to ~4 microns. PIXE revealed trace or minor elements undetectable by SEM-ED… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 19 publications
1
25
0
Order By: Relevance
“…The measured concentrations are quite different between EDS and PIXE. EDS consistently underestimates the Sn concentration, which is similar to previous comparison of EDS and PIXE for other kinds of materials [15]. The discrepancy for other elements does not show any clear tendency.…”
Section: Eds and Pixesupporting
confidence: 88%
See 2 more Smart Citations
“…The measured concentrations are quite different between EDS and PIXE. EDS consistently underestimates the Sn concentration, which is similar to previous comparison of EDS and PIXE for other kinds of materials [15]. The discrepancy for other elements does not show any clear tendency.…”
Section: Eds and Pixesupporting
confidence: 88%
“…Furthermore, the proton beam can be focused so that local composition in micro-meter scale can be probed. Therefore, the PIXE technique gives more accurate results with high sensitivity and spatial resolution and has been used in various elemental analysis applications [14,15]. In this work, we compared PIXE measurements with EDS results from CZTSe samples and found that the PIXE results are more consistent with photoluminescence (PL) and Raman spectroscopy measurements.…”
Section: Introductionmentioning
confidence: 82%
See 1 more Smart Citation
“…PIXIE has been shown to be effective for trace element profiling of gunshot residues. [6] Fourier Transform Infra-red (FTIR) and Raman spectroscopy are often combined with microscopy to provide techniques for establishing the composition of small fragments or particles. A summary of these techniques is shown in Fig.…”
Section: Chemical Forensic Sciencementioning
confidence: 99%
“…SEM-EDS therefore cannot discriminate many modern primers, limiting its usefulness for forensic evidence. We have already shown that IBA can give very sensitive quantitative information on many types of primer ( [61] [62]) thereby giving IBA increased discrimination power over SEM-EDS.…”
Section: Iba For Accurate (Traceable) Analysismentioning
confidence: 99%